Leveraging transcranial ultrasound stimulation to enhance self-regulation in emotion and sleep - Dunsford, Suraya; Komarnyckyj, Mica; Fouragnan, Elsa (Frontiers in Human Neuroscience, 2025)
This Perspective article discusses the emerging potential of transcranial ultrasound stimulation (TUS) as a non-invasive neuromodulatory technique for enhancing self-regulatory processes, particularly emotion and sleep regulation, in healthy individuals. Offering high spatial precision and the ability to target both cortical and deep brain regions, TUS uses focused ultrasound waves to induce acute and delayed effects on brain activity. We propose that combining TUS with neurofeedback methods and/or specific cognitive training exercises may capitalise on these neuroplastic effects, thereby augmenting and prolonging their impact to support lasting improvements in self-regulation. We focus on the domains of sleep and emotion regulation, where such an integrated approach may strengthen resilience and promote healthier functioning in the general population. Our aim is to highlight the potential of TUS-based integrated interventions for supporting mental health and well-being in non-clinical populations and to outline key directions for future research.